2017
DOI: 10.1093/ndt/gfx247
|View full text |Cite
|
Sign up to set email alerts
|

Etiology and renal outcomes of acute tubulointerstitial nephritis: a single-center prospective cohort study in China

Abstract: Our data demonstrate that autoimmune-related ATIN may present with systemic manifestations after kidney injury and is, therefore, commonly misdiagnosed. Repeated kidney injury is not uncommon in patients with ATIN. Scheduled follow-up is, therefore, critical for defining the exact etiology and proper management of ATIN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
46
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 27 publications
2
46
0
Order By: Relevance
“…In SS, IgG4-RD, and ATIN because of other causes, this susceptibility in HLA-DQA1, -DQB1, and -DRB1 alleles was not detected nor has it been reported elsewhere. Our recently published study found that 60% of patients with TINU syndrome had a history of taking causative drugs, presented allergic symptoms, and had late-onset uveitis (29). Other researchers have also reported cases of TINU syndrome induced by drugs (30) as well as positive drug-specific lymphocyte stimulating tests (31).…”
Section: Discussionmentioning
confidence: 93%
“…In SS, IgG4-RD, and ATIN because of other causes, this susceptibility in HLA-DQA1, -DQB1, and -DRB1 alleles was not detected nor has it been reported elsewhere. Our recently published study found that 60% of patients with TINU syndrome had a history of taking causative drugs, presented allergic symptoms, and had late-onset uveitis (29). Other researchers have also reported cases of TINU syndrome induced by drugs (30) as well as positive drug-specific lymphocyte stimulating tests (31).…”
Section: Discussionmentioning
confidence: 93%
“…Acute tubulointerstitial nephritis accounts for 1–3% of all renal biopsies and represents one of the most common pathological changes contributing to renal parenchymal AKI in biopsied settings, with an increasing trend reported in recent years . In a recent published prospective cohort study that enrolled 157 cases of biopsy‐proven ATIN with various etiologies, a changing etiologic spectrum during the disease follow‐up course was reported . At the time of renal biopsy, 64.3% of the cases were identified as drug‐induced ATIN and autoimmune diseases were diagnosed in 22.3% of the patients.…”
Section: Acute Tubulointerstitial Nephritismentioning
confidence: 99%
“…The major reason for this change was the misdiagnosis of tubulointerstitial nephritis and uveitis (TINU) syndrome, a previously thought rare autoimmune‐related ATIN, at the time of renal biopsy (8.9–22.3%). Of the patients whose final diagnosis was TINU syndrome, 60.0% had late‐onset uveitis and therefore were misclassified as drug‐induced ATIN since many of these had taken various medications before and during the onset of their diseases …”
Section: Acute Tubulointerstitial Nephritismentioning
confidence: 99%
See 2 more Smart Citations